Verbal autopsy of neonatal and infant deaths from Bhavnagar rural and comparison with recent data - Patel, Rajesh B.; Sinol, Hinal A.; Jindal, Sonal V.; Gohil, Jayendra R. (International Journal Of Community Medicine And Public Health, 2020)
Background: Infant deaths from Bhavnagar rural areas were studied by using a verbal autopsy tool. Methods: Community visit based retrospective study of Bhavnagar rural by WHO verbal autopsy questionnaire. Results: Of the 92 deaths analyzed, 59 % (early), 12% (late), and 29% were during the post neonatal period. Male deaths were 55 (60%). The most common immediate causes were infection (39%), birth asphyxia (23%), and hyaline membrane disease (15%). Underlying causes were: maternal illness with feeding problem (45%), prematurity (26%), meconium aspiration syndrome (9%), and congenital/genetic anomalies (10%). Infant and neonatal deaths were seen more with illiteracy of mother, age of mother (25-29 years), third parity, anemia, and vaginal discharge; and non-breastfed, low birth weight and preterm. Birth asphyxia and hyaline membrane disease were during early, and meningitis and pneumonia were after the neonatal period. Verbal autopsy was accurate in 18/23 (78%) of the facility-based deaths where the cause of death was available. Ethics approval was obtained. Conclusions: Reproductive health education to adolescent girls and mothers, regarding the treatment of fever, vaginal discharge; and breastfeeding counselling with vitamin B12 should be used as more infant deaths are associated with anemia of mother. Health workers should be skilled in neonatal resuscitation, prematurity management, and referral, after stabilization, identification of congenital anomaly, antenatal screening by USG, and neonatal metabolic screen. Recent 2018 data obtained from Bhavnagar District Health Authority shows that over a period of eight years, institutional deliveries have increased and home deliveries, early neonatal deaths, HMD, and septicemia have decreased. Perinatal care should be check-list based, monitored, and mentored.